2011
DOI: 10.3322/caac.20095
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) polymerase (PARP) inhibitors: Exploiting a synthetic lethal strategy in the clinic

Abstract: Poly(ADP-ribose) polymerase (PARP) is an attractive antitumor target because of its vital role in DNA repair. The homologous recombination (HR) DNA repair pathway is critical for the repair of DNA double-strand breaks and HR deficiency leads to a dependency on error-prone DNA repair mechanisms, with consequent genomic instability and oncogenesis. Tumor-specific HR defects may be exploited through a synthetic lethal approach for the application of anticancer therapeutics, including PARP inhibitors. This theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
144
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(144 citation statements)
references
References 136 publications
(212 reference statements)
0
144
0
Order By: Relevance
“…These observations indicate that inhibition of PARP-1 may cause disturbances in gene expression that may drive the stimulation of a genetic network that enhances oncogenic potential. More intriguingly, several preclinical studies have reported that PARP inhibitors are more effective in BRCA-deficient cells than in wild-type BRCA cells (Yap et al, 2011). Furthermore, a recent trial showed that iniparib failed to prolong survival in metastatic, triple-negative breast cancer (O'Shaughnessy et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations indicate that inhibition of PARP-1 may cause disturbances in gene expression that may drive the stimulation of a genetic network that enhances oncogenic potential. More intriguingly, several preclinical studies have reported that PARP inhibitors are more effective in BRCA-deficient cells than in wild-type BRCA cells (Yap et al, 2011). Furthermore, a recent trial showed that iniparib failed to prolong survival in metastatic, triple-negative breast cancer (O'Shaughnessy et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PARP inhibitors are developed to target a wide spectrum of cancers or to sensitize cancer cells to anticancer therapy. A variety of PARP-1 inhibitors, including Iniparib, Olaparib and Veliparib, are currently in clinical trials (Yap et al, 2011). However, much attention should be given to our observation that knockdown or chemical inhibition of PARP1 decreased the 5-FU-induced p53 binding on the promoter of MTA1, and subsequently recovered the expression level of the MTA1 gene (Figures 5c and 6a).…”
Section: Discussionmentioning
confidence: 99%
“…PARP inhibitors could restore BRCA1/2 function through genetic or epigenetic mechanisms [60]. Long-term PARP inhibition per se is also cause of tumor resistance, possibly through PARP gene mutations that alter interaction with inhibitors, or up-regulation of alternative DNA repair or cell proliferation pathways [61]. In summary, PARP inhibitors, the leading agents of synthetic lethality, are precious tools for killing tumor cells after the acquisition of resistance to previously employed therapies.…”
Section: Beyond Platinum-based Chemotherapy: Towards a Personalized Tmentioning
confidence: 99%
“…Based on this principle, PARP1/2 inhibitors (PARPi) have been developed to target tumor cells in BRCA1/2 mutation carriers, in which loss-of-function of both HR and base excision repair leaves DNA doublestrand breaks unrepaired, leading to accumulation of DNA damage, genomic instability and ultimately cell death (Bryant et al 2005, Farmer et al 2005, Sandhu et al 2010, Yap et al 2011, Dhillon et al 2016. Moreover, PARPi exert direct DNA toxicity by trapping PARP1 (and PARP2) at damaged DNA where the PARP-DNA complexes are more cytotoxic than unrepaired single-strand DNA breaks themselves (Murai et al 2012).…”
Section: Development Of Parp Inhibitors For Patients With Brca2-assocmentioning
confidence: 99%